Combining E-PASS model and disease specific risk factors to predict severe morbidity after liver and bile duct resection for perihilar cholangiocarcinoma. Issue 3 (March 2021) - Efanov, Mikhail; Alikhanov, Ruslan; Zamanov, Ekhtibar; Melekhina, Olga; Kulezneva, Yuliya; Kazakov, Ivan; Vankovich, Andrey; Koroleva, Anna; Tsvirkun, Victor
Abstract: Background: Estimation of physiologic ability and surgical stress system (E-PASS) has been shown to be effective in predicting morbidity after surgery for perihilar cholangiocarcinoma (PHCC). Nevertheless, E-PASS does not include an assessment of the disease specific risk factors. The aim of the study was to estimate the combined impact of E-PASS and specific preoperative factors on major morbidity for PHCC patients. Methods: A retrospective analysis of a prospectively collected data was performed. Severe morbidity according to complication comprehensive index was defined as ≥40 points. A value of comprehensive risk score (CRS) ≥1 was taken as critical. Results: Multivariate analysis of perioperative data from 122 patients revealed significant impact of five factors (CRS ≥1, future liver remnant volume <50%, T4 stage, moderate and severe cholangitis, INR) on the risk of severe morbidity after resection. The AUC for the combination of these factors was classified as good predictive value (0.810, 95% CI 0.729–0.891) and poor predictive value (0.673, 95% CI 0.573–0.773) for CRS alone (p = 0.040). Conclusion: A combination of E-PASS with disease specific risk factors is a reliable predictive model for major morbidity for patients undergoing radical surgery for PHCC.